Mechanical properties of Macadamia nutshell powder and PLA bio-composites - Dong, Jonathan; Davies, Ian; Fornari Junior, C.; Scaffaro, R. (Engineers Media Pty Ltd., 2016)
© 2016 Engineers AustraliaA study on the mechanical properties of Macadamia nutshell powder/PLA bio-composites is presented in this paper. The effects of powder weight content, powder condition and processing methods are investigated with the aid of Design of Experiments. It is shown from the results that both the stiffness and strength are dependent on the weight content of Macadamia nutshell powders. The elastic modulus increases 9.8% when the Macadamia nutshell powder content is 40%. Both flexural and tensile strengths decrease with increasing Macadamia nutshell powder content. On average, when the Macadamia nutshell powder content is 40%, the decreases in the flexural and tensile strengths are 42 and 63%, respectively, compared to pure PLA. The hardness is independent of the weight content of nutshell powders.